Prestasi Belajar Siswa Sekolah Dasar dalam Kaitannya dengan Pola Asuh Nenek Di Kelurahan Sapan Kabupaten Toraja Utara - Novalia Sulastri; Sefrin Siang Tangkearung (Jurnal Keguruan dan Ilmu Pendidikan, 2022)
The problem in this study is what parenting patterns are used by grandmothers in caring for their grandsons who excel in Sapan Village. This study uses an approach with a descriptive type of research. This research instrument uses data collection through observation, interviews and documentation. The main subjects in this study were 5 grandmothers and 5 grandchildren in Sapan village. The results of the research conducted by this researcher indicate that: 1) The parenting pattern used by grandmothers in Sapan Village is a permitted and democratic parenting pattern, 2) Factors that cause parenting to switch to existing ancestors due to economic factors, busy parents working, widowed or widowed parents due to death and divorced parents.